Advances in Scanning Transmission X‐Ray Microscopy for Elucidating Soil Biogeochemical Processes at the Submicron Scale. Issue 6 (1st November 2017) - Stuckey, Jason W.; Yang, Jianjun; Wang, Jian; Sparks, Donald L.
Abstract : Organic matter, minerals, and microorganisms are spatially associated in complex organo‐mineral assemblages within soils. A mechanistic understanding of processes occurring within organo‐mineral assemblages requires noninvasive techniques that minimize any disturbance to the physical and chemical integrity of the sample. Synchrotron‐based soft (50–2200 eV) X‐ray spectromicroscopic techniques, including scanning transmission X‐ray microscopy (STXM), transmission X‐ray microscopy (TXM), X‐ray photoemission electron microscopy (X‐PEEM), and scanning photoelectron microscopy (SPEM), coupled with microspectroscopy (e.g., near‐edge X‐ray absorption fine structure; NEXAFS) allow for determining the spatial association and speciation of most elements found in soils while maintaining sample integrity. This review highlights application of the four spectromicroscopic techniques mentioned above to soil biogeochemical research, with particular emphasis on STXM‐NEXAFS, which has contributed to the greatest set of advancements in the understanding of soil organo‐mineral interactions, including mineral control on organic carbon cycling and the mechanisms of biomineral formation. Core Ideas: Analysis of soil processes requires techniques able to speciate light and heavy elements. STXM‐NEXAFS determines the speciation of spatially associated light and heavy elements. STXM‐NEXAFS enables elucidation of microaggregate and biomineral formation mechanisms. Advances in synchrotron‐based STXM will allow for wavelength‐limited spatial resolution.